A Mixed-Method Study of Burnout Among American Pastoral Musicians - Behel, Kensley (Pastoral psychology, 2025)
Occupational burnout is a concern for the health of clergy and musicians and the longevity of their careers. However, no known study has assessed occupational burnout among pastoral musicians in the United States. Therefore, the aims of this paper were to (1) describe pastoral musicians as a population, (2) identify the prevalence rate of burnout among pastoral musicians, and (3) investigate the relationship between pastoral musicians’ burnout and religious coping. In 2021, an online questionnaire designed to assess burnout among pastoral musicians was disseminated via email to members of the Hymn Society of North America and via social media to collect data from pastoral music directors in the United States. The survey yielded N = 1,050 respondents. Of these, 83.8% experienced one or more symptoms of burnout (41.3% with low efficacy; 12.4% with high emotional exhaustion; 21.3% with high cynicism; 8.8% with burnout). Ineffectiveness was positively correlated with negative religious coping. Emotional exhaustion and cynicism were positively correlated with negative religious coping. This study contributes quantitative analysis to pastoral musician research. Findings demonstrate that burnout is prevalent among American pastoral musicians. More research is needed to investigate solutions for burnout among this population.Keywords: church musician, performance-related health problems (PRHPs), clergy, musicians’ health, performing arts health, burnout.